PERBEDAAN KADAR INTERLEUKIN-6 PADA BERBAGAI STADIUM KLINIS KANKER PAYUDARA - , Ani Uswatun Chasanah; , dr. Andaru Dahesihdewi, M.Kes, SpPK(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Breast cancer is one of the many diseases that cause morbidity and mortality. The prevalence of breast cancer is increasing worldwide including in Indonesia along with increased life expectancy, socioeconomic, and changes in disease patterns. More than half of patients with breast cancer was diagnosed in an advanced stage when the tumor has had metastasis to the handling tends to be late and only palliative. The biology of breast cancer is complex, involving oncogenesis, evasion of host immune defense mechanisms, angiogenesis, invasion and metastasis. So far, interleukin-6, better known as cytokines that mediate inflammation and activation of lymphocytes hematopoesis, but recent studies reported IL-6 has a role as a mediator of tumor progression. IL-6 expression correlated with the degree of tumor, and poor survival. The results of these studies enabled the development of new therapeutic anti-IL-6 to improve the existing therapy. This study is an observational analytic study with a cross-sectional design to determine differences in levels of IL-6 at various clinical stages of breast cancer. The subjects in this study were consecutive patients with suspected breast cancer that visited the oncology clinic Tulip or pre-operative patients in the surgical treatment of Dr. Sardjito hospital in Yogyakarta who fullfilled the inclusion and exclusion criteria. Examination of IL-6 serum using a quantitative sandwich electrochemiluminescence immunoassay method. The results shown in the descriptive analysis and analysis of differences in levels at various clinical stages.